USE OF CELLULAR CONCRETE FOR AIR CONVECTION EMBANKMENT TO PROTECT PERMAFROST FOUNDATION IN COLD REGIONS - Wu, Hanli (Scholars' Mine, 2022)
"Crushed-rock air convection embankment (ACE) has been used to mitigate thaw settlement, and pavement distresses caused by climatic extremes in permafrost regions for over three decades. However, the desired crushed rocks needed for ACE are not readily available in many areas of interior Alaska. Burdened by the need to ship suitable rocks to remote locations, the cost of constructing an ACE is often prohibitively high, which prevents its wide use in Alaska. An existing cementitious material, cellular concrete, may provide the solution. This study intends to systematically characterize the heat transfer patterns of ACE and identify the performance benefits of using cellular concrete for ACE through material laboratory tests, modeling, and numerical simulation. A feasibility study on the use of cellular concrete as an alternative material for ACE was conducted. The impacts of lightweight aggregate ACE on the overall pavement performance were evaluated. The design configurations of cellular concrete block ACE were further designed to maximize performance benefits and facilitate future implementation and field construction. The studies presented in this work show that the thermal stability and preliminary cost-benefit of cellular concrete ACE were superior to the conventional embankments. Cellular concrete aggregate ACE could effectively mitigate moisture warping and temperature curling of the asphalt concrete layer. The proposed hollow cellular concrete block ACEs significantly accelerated the air convection in the embankment in winter and improved the heat insulation effect of the pavement structures in summer. Which significantly mitigated the thaw settlement of ice-rich subgrade in permafrost regions"--Abstract, p. iv